Understanding, oral hygiene practices, behaviors and myths to deal with Toothache in Rural areas - Sarang Suresh Hotchandani; Priya Rani Harjani; Suneel Kumar Punjabi; Mowaffaq Abdullmomen Al Absi; Hafiz Mahmood Azam; Ahmed, Aswad (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: In Pakistan, there is lack of awareness to maintain oral hygiene and cleaning of oral structures. The current study aims to unveil homemade remedies and self-care methods followed by a majority of the rural population to cure dental pain in Sindh, Pakistan. METHODOLOGY: This cross-sectional descriptive study was conducted at dental OPD of the Secondary Health Care Facility of Sindh, Pakistan, by following a random sample selection approach. Patients from both genders representing oro-dental problems of ages ≥ 5 year were included in the study. Patient’s clinical and demographic data was collected, and further descriptive data analysis was done by using Microsoft Excel 2016. RESULTS: A total of 1627 patients fulfilled the inclusion criteria of the study. The highest number of cases (73.81%) were belonging to the age group 15-49 years, affirming that adults are at greater risk of developing toothache and dental pain. Surprisingly, about 78.97% patients had never visited any physician for seeking the clinical services. Similarly, 37.18 % of patients did not use any cleaning substance while 22.12 % patients preferred miswak for cleaning of their teeth. Only 2.95 % of patients visited dentists for proper care. CONCLUSION: Current research report concludes that from all the confirmed toothache cases, 22.13 % of patients sought care from general physicians in parallel with 22.34 % patients were preferring religious spells to manage their dental pain, which further multiplied the disease rate. However, general physicians at primary healthcare settings have limited knowledge and training in managing dental pain.